Preparation method of hydrotalcite-like material, hydrotalcite-like material and carbon dioxide adsorption material

By regulating the amount and concentration of the first acid in acid treatment, combined with alkali treatment and aging treatment, efficient hydrotalcite-like materials are prepared, which solves the problems of waste of chemical reagents and low material conversion rate, and realizes efficient recycling of chemical reagents. and high conversion rate of materials.

CN119349619APending Publication Date: 2025-01-24SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411411203.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the process of preparing hydrotalcite-like materials, more chemical reagents are used in the prior art, which leads to waste of chemical reagents and affects the conversion rate and recyclability of the material.

Method used

By regulating the amount and concentration of the first acid, acid treatment is performed to break the M-O chemical bonds on the surface of the solid waste material, improve the chemical reaction activity, and combine alkaline treatment and aging treatment to form high-efficiency water-like materials preparation methods.

Benefits of technology

This method effectively reduces the waste of chemical reagents, enhances the conversion rate of water -like talc materials and the recycling of the first alkali, and improves the industrial application value of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349619A_ABST
    Figure CN119349619A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydrotalcite-like material, the hydrotalcite-like material and a carbon dioxide adsorption material.The preparation method of the hydrotalcite-like material comprises the following steps that acid treatment is conducted, specifically, a solid waste material and first acid with the volume fraction being 20%-40% are mixed and ground according to the mass ratio of 1: (0.7-5), pretreated slurry with the pH being 5-7 is obtained, and the pretreated slurry is dried; wherein the solid waste material comprises divalent metal elements and trivalent metal elements; alkali treatment: mixing the pretreated slurry with first alkali for reaction, and then performing aging treatment to obtain the hydrotalcite-like material. According to the preparation method of the hydrotalcite-like material, the consumption of the first alkali reagent can be reduced, the recyclability of the first alkali reagent can be improved, meanwhile, the conversion rate of the hydrotalcite-like material can also be improved, and the preparation method has important guiding significance on industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solar cells, and in particular to a preparation method of a hydrotalcite-like material, a hydrotalcite-like material and a carbon dioxide adsorption material. Background Art

[0002] Blast furnace slag is a typical solid waste of industrial production. Related research processes blast furnace slag into hydrotalcite-like materials. When this material is heated to 400°C, it can remove interlayer water molecules and convert metal hydroxides into hydrotalcite-like materials. Hydrotalcite-like materials can effectively adsorb CO2 at around 200°C and have high industrial application value.

[0003] In the process of preparing hydrotalcite-like materials using blast furnace slag as raw material, it needs to undergo acid treatment and alkali treatment in sequence. In order to improve the conversion rate of hydrotalcite-like materials, more chemical reagents are used in the above acid treatment or alkali treatment, resulting in waste of chemical reagents. Summary of the invention

[0004] In order to reduce the waste of chemical reagents in the process of preparing a hydrotalcite-like material, the present invention provides a method for preparing a hydrotalcite-like material, a hydrotalcite-like material, and a carbon dioxide adsorption material.

[0005] In a first aspect, an embodiment of the present invention provides a method for preparing a hydrotalcite-like material.

[0006] A method for preparing a hydrotalcite-like material comprises the following steps:

[0007] Acid treatment: mixing and grinding the solid waste material and a first acid having a volume fraction of 20% to 40% in a mass ratio of 1:(0.7 to 5) to obtain a pretreated slurry having a pH of 5 to 7, wherein the solid waste material contains a divalent metal element and a trivalent metal element;

[0008] Alkali treatment: the pretreated slurry is mixed with a first alkali for reaction, and then subjected to aging treatment to obtain a hydrotalcite-like material.

[0009] As an optional implementation, in an embodiment of the present invention, the first acid is a small molecule organic acid, and the small molecule organic acid includes one or more of acetic acid or butyric acid.

[0010] As an optional implementation, in an embodiment of the present invention, the first base is an inorganic base containing hydroxide ions, and the inorganic base is one or more of sodium hydroxide or potassium hydroxide.

[0011] As an optional implementation manner, in an embodiment of the present invention, the concentration of the first alkali is 1-4 mol / L, and the input ratio of the solid waste material to the first alkali is 1 g: (6-60) mL.

[0012] As an optional implementation, in an example of the present invention, after the aging treatment, the first alkali is recovered, and the recovered first alkali is recycled for use in preparing the hydrotalcite-like material.

[0013] As an optional embodiment, in an embodiment of the present invention, in the acid treatment step, the grinding time is 0.5 to 2 hours, and the grinding speed is 300 to 800 rpm; and / or, in the alkali treatment step, the temperature of the mixed reaction of the pretreated slurry and the first alkali is 90°C to 100°C, and the time is 0.5 to 2 hours; and / or, in the alkali treatment step, the aging treatment is room temperature aging for more than 12 hours.

[0014] As an optional implementation, in an embodiment of the present invention, the method for preparing the hydrotalcite-like material further comprises the following steps:

[0015] After the aging treatment, the intercalation anion treatment is added:

[0016] The hydrotalcite-like material after the aging treatment is mixed with an organic anion metal salt solution and placed in a protective atmosphere of nitrogen or inert gas, and reacted at 140° C. to 180° C. for 12 to 24 hours to obtain the hydrotalcite-like material with changed intercalated anions.

[0017] As an optional embodiment, in an embodiment of the present invention, the organic anion in the organic anion metal salt is one or more of butyrate ion or acetate ion; and / or, 10g of the hydrotalcite-like material after the aging treatment is added to every 1L of the organic anion metal salt solution, and the concentration of the organic anion metal salt solution is 0.1-5mol / L; and / or, after the intercalation anion treatment is changed, the organic anion metal salt solution is recovered, and the recovered organic anion metal salt solution is recycled in the step of changing the intercalation anion treatment.

[0018] As an optional implementation, in an embodiment of the present invention, the average particle size of the solid waste material is 1 to 100 μm.

[0019] In a second aspect, an embodiment of the present invention provides a hydrotalcite-like material.

[0020] A hydrotalcite-like material is prepared by the preparation method of a hydrotalcite-like material as described in the first aspect, and the hydrotalcite-like material comprises an alkali silicate and a layered double metal hydroxide, wherein the layered double metal hydroxide is supported on the surface of the alkali silicate.

[0021] As an optional embodiment, in an embodiment of the present invention, the layered double hydroxide includes divalent metal ions, trivalent metal ions and intercalation anions, the divalent metal ions include one or both of calcium ions or magnesium ions, the trivalent metal ions include aluminum ions, and the intercalation anions include one or more of silicate ions, butyrate ions or acetate ions.

[0022] In a third aspect, an embodiment of the present invention provides a carbon dioxide adsorption material.

[0023] As an optional embodiment, in an embodiment of the present invention, the hydrotalcite-like material as described in the second aspect is used, and the carbon dioxide adsorption material includes an alkali silicate and a layered bimetallic oxide, and the layered bimetallic oxide is loaded on the surface of the alkali silicate, and the layered bimetallic oxide presents a nano-petal-like morphology.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention provides a method for preparing a hydrotalcite-like material. In the process of preparing the hydrotalcite-like material, by adjusting the dosage and concentration of the first acid, the surface of the solid waste material is contacted with the first acid with relatively weak acidity to react, so as to achieve the purpose of breaking the M (metal)-O chemical bond on the surface of the solid waste material, and improve the chemical reaction activity of the solid waste material. Combined with the grinding process, the refinement and cracking of the granular solid waste material are promoted, the breaking of the MO bond is aggravated, and a virtuous cycle is formed. Therefore, the present invention can obtain a pre-treated slurry with neutral or weak acidity and high chemical reaction activity by adding a specific dosage and a specific concentration of the first acid to mix with the solid waste material and grind it.

[0026] In the subsequent alkali treatment stage, the pre-treated slurry reacts rapidly with the first alkali to form a precipitate due to its high activity, and the precipitation process and the integrity of the hydrotalcite-like material structure are strengthened through aging treatment, effectively improving the conversion rate of the hydrotalcite-like material. Since the pre-treated slurry is neutral or slightly acidic, it is beneficial to reduce the over-consumption of the first alkali caused by the acid-base neutralization reaction, thereby improving the recyclability of the first alkali and reducing the waste of chemical reagents. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 is the XRD diagram of the hydrotalcite-like material disclosed in Example 1 of the present invention;

[0029] Figure 2 is a SEM image of the hydrotalcite-like material disclosed in Example 1 of the present invention;

[0030] Figure 3 It is a comparison chart of the pH test results of the pretreated slurry disclosed in Example 1, Example 2, Example 3 and Comparative Example 2 of the present invention;

[0031] Figure 4 is a comparison chart of the carbon dioxide chemical adsorption amount of the hydrotalcite-like materials disclosed in Examples 1 to 6 and Comparative Examples 1 to 3 after activation;

[0032] Figure 5 It is a comparison chart of the total carbon dioxide adsorption after activation of Example 1, Example 2, Example 6 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the present invention, the directions or positional relationships indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like are based on the directions or positional relationships shown in the drawings. These terms are mainly used to better describe the present invention and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific direction, or to be constructed and operated in a specific direction.

[0035] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those skilled in the art, the specific meanings of these terms in the present invention can be understood according to specific circumstances.

[0036] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0037] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0038] Solid waste materials, as a typical industrial solid waste, are by-products produced during the steel smelting process. Their main components are mixed metal oxides such as calcium, magnesium and aluminum, and various metal silicates. The chemical activity of solid waste materials themselves is low, and metal elements are generally difficult to directly react with alkali solutions to form metal hydroxides. In the process of preparing hydrotalcite-like materials, acid treatment is generally used to digest solid waste materials, so that the metal elements in the solid waste materials are precipitated in the form of metal ions, and an acid solution containing metal ions is obtained by filtration. Then, under heating conditions, an alkaline reagent is dripped into the acid solution containing metal ions to convert the environment of the acid solution into an alkaline solution with a pH value of more than 10, and the preparation of hydrotalcite-like materials is completed by stirring and heating at a temperature of about 100°C, followed by aging treatment at room temperature.

[0039] In order to improve the conversion rate of hydrotalcite-like materials, more acid reagents are generally used in the acid treatment process to increase the precipitation of metal ions and increase the concentration of metal ions in the acid solution containing metal ions. However, excessive use of acid reagents can easily lead to a neutralization reaction between the alkali reagent and the excess acid reagent during the subsequent alkali treatment process, resulting in excessive consumption of the alkali reagent.

[0040] To this end, the present invention provides a method for preparing a hydrotalcite-like material, a hydrotalcite-like material, and a carbon dioxide adsorbing material. The method for preparing the hydrotalcite-like material can reduce the consumption of the alkali reagent, improve the recyclability of the alkali reagent, and also improve the conversion rate of the hydrotalcite-like material, which has important guiding significance for industrial production.

[0041] The technical solution of the present invention will be further described below in conjunction with embodiments.

[0042] In a first aspect, an embodiment of the present invention provides a method for preparing a hydrotalcite-like material.

[0043] A method for preparing a hydrotalcite-like material comprises the following steps:

[0044] Acid treatment: mixing and grinding the solid waste material and a first acid having a volume fraction of 20% to 40% in a mass ratio of 1:(0.7 to 5) to obtain a pretreated slurry having a pH of 5 to 7, wherein the solid waste material contains a divalent metal element and a trivalent metal element;

[0045] Alkali treatment: the pre-treated slurry is mixed with the first alkali for reaction, and then subjected to aging treatment to obtain a hydrotalcite-like material.

[0046] The present invention achieves mild acidification of the surface of solid waste materials by regulating the dosage and concentration of the first acid, promotes the effective breaking of the M (metal)-O chemical bond, and significantly improves the chemical reactivity of the solid waste materials. Furthermore, combined with the grinding treatment, the refinement and cracking of the granular solid waste materials are promoted, the breaking of the MO bond is aggravated, a virtuous cycle is formed, and the activation process of the solid waste materials is accelerated. Finally, a pre-treated slurry with neutral or slightly weak acidity and high chemical reactivity is obtained.

[0047] In the subsequent alkali treatment stage, the pre-treated slurry reacts rapidly with the first alkali to form a precipitate due to its high activity, and the precipitation process and the integrity of the hydrotalcite-like material structure are strengthened through aging treatment, effectively improving the conversion rate of the hydrotalcite-like material. Since the pre-treated slurry is neutral or slightly acidic, it is beneficial to reduce the over-consumption of the first alkali caused by the acid-base neutralization reaction, thereby improving the recyclability of the first alkali and reducing the waste of chemical reagents.

[0048] It is understandable that in the present invention, the first acid and the surface of the solid waste material only need to break the MO chemical bond, and there is no need to digest the solid waste material until the metal components are completely dissolved and precipitated in the form of metal ions. In addition, the present invention uses the pre-treated slurry in a solid-liquid mixed state to directly react with the first alkali without going through intermediate treatment steps such as filtration, which can reduce the preparation steps while ensuring a high conversion rate. In addition, the metal elements in the pre-treated slurry can be further activated in the alkali treatment step to increase the generation of metal precipitation and improve the conversion rate of the hydrotalcite-like material.

[0049] In the present invention, the consumption of the first alkali is small and can be recycled multiple times. If the first acid is used in excessive amounts or at too high a concentration, the pH value of the pre-treated slurry after grinding is too low, which may cause the first alkali to be consumed excessively due to the acid-base neutralization reaction, resulting in a decrease in the recyclability of the first alkali. If the first acid is used in too little amounts or at too low a concentration, the conversion rate of some metal elements in the solid waste may decrease, or the first acid may react with carbon dioxide in the air in advance, which may be detrimental to the carbon dioxide adsorption effect of the hydrotalcite-like material.

[0050] Preferably, the solid waste material of the present invention is a material containing blast furnace slag. Blast furnace slag is a molten material with silicate and calcium aluminosilicate as the main components obtained during the blast furnace iron smelting process. Blast furnace slag is rich in divalent metal elements and trivalent metal elements such as calcium, magnesium or aluminum. These divalent metal elements and trivalent metal elements can be directly used in the preparation of hydrotalcite-like materials. In addition, blast furnace slag can also be flexibly used in combination with other solid waste materials, such as solid waste materials containing divalent metal elements (such as calcium oxide, calcium silicate or calcium aluminosilicate) or solid waste materials containing trivalent metal elements (such as red mud), or solid waste materials containing divalent metal elements and solid waste materials containing trivalent metal elements are mixed and directly used as solid waste materials for preparing hydrotalcite-like materials, so as to achieve the purpose of providing the required metal elements for preparing hydrotalcite-like materials.

[0051] In some embodiments, the first acid is a small molecule organic acid.

[0052] The advantages of using a small molecule organic acid as the first acid are as follows: first, the organic group in the small molecule organic acid can improve the grinding efficiency, which is beneficial to improving the chemical activity of the pretreatment slurry; second, the above-mentioned hydrotalcite-like material is used to capture carbon dioxide. Compared with large molecule organic acids, the use of small molecule organic acids can reduce the additional carbon dioxide release caused by the carbonization of organic matter during the subsequent calcination of the hydrotalcite-like material; third, the use of small molecule organic acids is beneficial to controlling the acidity of the pretreatment slurry after grinding, and can avoid the acidity of the pretreatment slurry after grinding being too strong while leaching a certain amount of divalent metal elements and trivalent metal elements, resulting in excessive loss of the first alkali due to the acid-base neutralization reaction during the subsequent alkali treatment, resulting in a decrease in the recyclability of the first alkali.

[0053] Preferably, the small molecule organic acid comprises one or more of acetic acid or butyric acid.

[0054] These acid reagents can not only better meet the use requirements of the present invention, but also have relatively low costs, which is conducive to reducing production costs.

[0055] In some embodiments, the first base is an inorganic base containing hydroxide ions.

[0056] By adding the first alkali, the pretreated slurry can form a metal hydroxide precipitate in an alkaline environment, and then age to form a hydrotalcite-like material. Exemplarily, the first alkali is one or more of sodium hydroxide or potassium hydroxide. Sodium hydroxide or potassium hydroxide can provide a better alkaline environment for the formation of hydrotalcite-like materials, and are cheap and easy to obtain, which is conducive to reducing production costs.

[0057] In some embodiments, the concentration of the first alkali is 1-4 mol / L, and the ratio of the input amount of the solid waste material to the first alkali is 1 g: (6-60) mL.

[0058] By controlling the amount of the first alkali, a strong alkaline environment is provided for the divalent metal elements and trivalent metal elements in the pretreatment slurry to fully react, thereby promoting the full formation of metal hydroxide precipitation, thereby improving the conversion rate of the hydrotalcite-like material.

[0059] In some embodiments, after the aging treatment, the first alkali is recovered and the recovered first alkali is recycled for use in preparing the hydrotalcite-like material.

[0060] The present invention controls the concentration and dosage of the first acid so that the pH of the pretreated slurry obtained by acid treatment is controlled between 5 and 7, which makes the amount of the first alkali consumed by acid-base neutralization with the first acid during the alkali treatment process lower. After the alkali treatment is completed, the first alkali still has a high alkalinity and can be recycled and reused to prepare a hydrotalcite-like material. Moreover, after the aging reaction is completed, unprecipitated metal ions still exist in the first alkali. The recovered first alkali is used to prepare a hydrotalcite-like material, which is conducive to further improving the conversion rate of the hydrotalcite-like material.

[0061] In some embodiments, in the acid treatment step, the grinding time is 0.5 to 2 hours, and the grinding speed is 300 to 800 rpm. Under the above grinding conditions, the surface of the solid waste material can be quickly broken, which promotes the rapid formation of the pre-treated slurry.

[0062] In some embodiments, in the alkali treatment step, the temperature of the pretreated slurry and the first alkali mixed reaction is 90°C to 100°C, and the time is 0.5 to 2 hours. Under the above alkali treatment environment, the precipitation reaction has a better effect, providing a favorable environment for the transformation and precipitation of metal elements, and promoting more metal elements to form hydrotalcite-like materials.

[0063] In some embodiments, in the alkali treatment step, the aging treatment is room temperature aging for more than 12 hours.

[0064] Aging at room temperature for more than 12 hours is conducive to the full progress of the precipitation reaction, providing additional time for the growth of hydrotalcite-like materials, promoting the improvement of the structure of hydrotalcite-like materials, forming a more stable and orderly structure, and reducing the risk of changes in hydrotalcite-like materials during subsequent processing and application. This helps to ensure the stability and reliability of hydrotalcite-like materials in practical applications.

[0065] In some embodiments, the method for preparing a hydrotalcite-like material further comprises the following steps:

[0066] After aging treatment, the intercalation anion treatment was added:

[0067] The hydrotalcite-like material after aging treatment is mixed with an organic anion metal salt solution and placed in a protective atmosphere of nitrogen or inert gas, and reacted at 140° C. to 180° C. for 12 to 24 hours to obtain a hydrotalcite-like material with changed intercalated anions.

[0068] The above method can change the intercalation anions of the hydrotalcite-like material. By changing the intercalation anions, the interlayer spacing of the hydrotalcite-like material can be regulated, thereby changing the surface physical and chemical properties of the hydrotalcite-like material after calcination and collapse, and ultimately improving the carbon dioxide adsorption efficiency.

[0069] In some embodiments, the organic anion in the organic anion metal salt is one or more of butyrate ion or acetate ion.

[0070] The organic anions in the organic anion metal salt are intercalation anions. Selecting one or more of butyrate ions or acetate ions as intercalation anions is beneficial to improving the adsorption efficiency of carbon dioxide.

[0071] Preferably, 10 g of the aged hydrotalcite-like material is added to every 1 L of the organic anion metal salt solution, and the concentration of the organic anion metal salt solution is 0.1 to 5 mol / L.

[0072] Preferably, after the intercalation anion treatment is changed, the organic anion metal salt solution is recovered and the recovered organic anion metal salt solution is recycled and used in the step of changing the intercalation anion treatment.

[0073] After the intercalation anion treatment is changed, the concentration of organic anions in the organic anion metal salt solution is still relatively high and can be recovered and recycled.

[0074] In some embodiments, the average particle size of the solid waste material is 1-100 μm.

[0075] The use of solid waste materials with an average particle size of 1 to 100 μm is conducive to sufficient grinding and uniform dispersion of the solid waste materials, and the solid waste materials are fully contacted with the first acid, which makes it easier to convert the solid waste materials into hydrotalcite-like materials in the subsequent treatment process.

[0076] In a second aspect, an embodiment of the present invention provides a hydrotalcite-like material.

[0077] The hydrotalcite-like material is prepared by the preparation method mentioned in the first aspect. The hydrotalcite-like material comprises alkali silicate and layered double metal hydroxide, and the layered double metal hydroxide is loaded on the surface of the alkali silicate.

[0078] In the hydrotalcite-like material obtained by the present invention, alkali silicate and layered double metal hydroxide are main components, wherein the layered double metal hydroxide plays a role in capturing carbon dioxide.

[0079] In some embodiments, the layered double hydroxide includes divalent metal ions, trivalent metal ions and intercalation anions, the divalent metal ions include one or both of calcium ions or magnesium ions, the trivalent metal ions include aluminum ions, and the intercalation anions include one or more of silicate ions, butyrate ions or acetate ions.

[0080] In a third aspect, an embodiment of the present invention provides a carbon dioxide adsorption material.

[0081] The carbon dioxide adsorbent material is made of the hydrotalcite-like material mentioned in the second aspect. The carbon dioxide adsorbent material comprises alkali silicate and layered bimetallic oxides, and the layered bimetallic oxides are loaded on the surface of the alkali silicate.

[0082] The hydrotalcite-like material is activated by calcination at 400°C. This process causes the layered double hydroxide to transform into an amorphous oxide structure. During this process, interlayer water and OH- are effectively removed, causing the layered structure to collapse and present a nano-petal-like morphology.

[0083] Importantly, calcination can also expose highly active divalent metal oxide sites, endowing the activated materials with significantly enhanced physical and chemical adsorption capabilities for CO2.

[0084] The technical solution of the present invention will be further described below in conjunction with more specific embodiments.

[0085] Embodiment 1

[0086] An embodiment of the present invention provides a method for preparing a hydrotalcite-like material, comprising the following steps:

[0087] Acid treatment: Put 5 g of blast furnace slag into a 50 mL alumina ball mill, add 4 1.5 cm diameter, 8 1 cm diameter, and 8 0.5 cm diameter zirconia ball milling beads, add 5 g of 40% acetic acid solution by volume, and ball mill at 600 rpm with a planetary ball mill for 2 h to obtain a pretreated slurry.

[0088] Alkali treatment: Take the pretreated slurry obtained in the above acid treatment step, add 100 mL of 1 mol / L NaOH solution, stir and heat to 95°C, react at 95°C for 2 hours, then stir and age at room temperature for 12 hours, filter to separate the solid and liquid, and dry the solid to obtain a hydrotalcite-like material.

[0089] Embodiment 2

[0090] The embodiment of the present invention provides a method for preparing a hydrotalcite-like material, which differs from the first embodiment in that in the acid treatment step, an acetic acid solution with a volume fraction of 20% is used instead of an acetic acid solution with a volume fraction of 40%, and the rest is consistent with the first embodiment.

[0091] Embodiment 3

[0092] The embodiment of the present invention provides a method for preparing a hydrotalcite-like material, which differs from the first embodiment in that in the acid treatment step, a hydrochloric acid solution with a volume fraction of 20% is used to replace an acetic acid solution with a volume fraction of 40%, and the rest is consistent with the first embodiment.

[0093] Embodiment 4

[0094] The embodiment of the present invention provides a method for preparing a hydrotalcite-like material, which is different from the first embodiment in that: in the acid treatment step, the ball milling time is 0.5 h, and the rest is consistent with the first embodiment.

[0095] Embodiment 5

[0096] The embodiment of the present invention provides a method for preparing a hydrotalcite-like material, which differs from the first embodiment in that: in the alkali treatment step, the liquid filtered in the first embodiment is used as the recovery solution, 100 mL of the recovery solution is used to replace 100 mL of 1 mol / L NaOH solution, and the rest is consistent with the first embodiment.

[0097] Embodiment 6

[0098] The embodiment of the present invention provides a method for preparing a hydrotalcite-like material, which is different from the first embodiment in that after the alkali treatment, a step of changing the intercalated anion is added, which is as follows:

[0099] Take a hydrotalcite-like material and add it to a hydrothermal reactor containing a sodium butyrate solution, wherein the molar ratio of the hydrotalcite-like material to the sodium butyrate is 1:5. Pre-pass argon protective gas for 10 minutes to exclude air, seal the hydrothermal reactor, and heat at 180° C. for 12 hours to obtain a hydrotalcite-like material with butyrate ions as intercalated anions.

[0100] Comparative Example 1

[0101] The comparative example of the present invention provides a method for preparing a hydrotalcite-like material, which is different from the first embodiment in that the acid treatment step is omitted, and the rest is consistent with the first embodiment.

[0102] Comparative Example 2

[0103] The comparative example of the present invention provides a method for preparing a hydrotalcite-like material, which is different from the first embodiment in that in the acid treatment step, pure water is used to replace the acetic acid solution with a volume fraction of 40%, and the rest is consistent with the first embodiment.

[0104] Comparative Example 3

[0105] The comparative example of the present invention provides a method for preparing a hydrotalcite-like material, which differs from the first embodiment in that in the acid treatment step, a hydrochloric acid solution with a volume fraction of 40% is used to replace an acetic acid solution with a volume fraction of 40%, and the rest is consistent with the first embodiment.

[0106] Experiment 1

[0107] Component analysis

[0108] The hydrotalcite-like material prepared in Example 1 was taken as a sample and analyzed using a Rigaku Smartlab X-ray diffractometer (XRD). The XRD pattern obtained by the test is shown in Figure 1 .

[0109] analyze Figure 1 From the XRD diagram, the peaks marked with spades represent layered double hydroxide components (Meixnerite, PDF#: 00-050-1684), and the peaks marked with squares represent alkali silicate components, proving that both layered double hydroxide components and alkali silicate components exist in the hydrotalcite-like material sample.

[0110] Experiment 2

[0111] The hydrotalcite-like material prepared in Example 1 was used as a sample, and the sample was heated at 400°C for 3 hours and observed using a high-resolution scanning electron microscope (Merlin, Zeiss). The test results are shown in Figure 2 .

[0112] Depend on Figure 2 It can be seen that after activation, a nano-petal-like structure is formed on the surface of the hydrotalcite-like material.

[0113] Experiment 3

[0114] 3.1 The pH value of the pretreated slurry prepared in Example 1, Example 2, Example 3 and Comparative Example 2 was tested. The test results are shown in Figure 3 .

[0115] exist Figure 3 In the figure, four pre-treated slurry photos are arranged from left to right, the pH test paper below the pre-treated slurry photos shows the corresponding pH test results, and the standard colorimetric card of the pH test paper is given at the bottom of the picture.

[0116] From the left, the first pretreatment slurry photo is the pretreatment slurry obtained in Example 1, with a pH of about 5, the third pretreatment slurry photo is the pretreatment slurry obtained in Example 2, with a pH of about 7, and the second pretreatment slurry photo is the pretreatment slurry obtained in Example 3, with a pH of about 7. During the alkali treatment process in Examples 1, 2 and 3, less sodium hydroxide solution is consumed, which is conducive to multiple recycling of the sodium hydroxide solution.

[0117] The fourth pretreatment slurry photo is the pretreatment slurry obtained in Comparative Example 1, with a pH of about 10, which indicates that the pH of the pretreatment slurry obtained by adding pure water for grinding is relatively high, and the activation effect of the metal elements in the pretreatment slurry is poor, which is not conducive to improving the conversion rate of hydrotalcite-like materials.

[0118] 3.2 Carbon dioxide capture effect test

[0119] 3.2.1 Chemical adsorption of carbon dioxide

[0120] The hydrotalcite-like materials prepared in the above examples and comparative examples were taken as samples, washed with ultrapure water until the surface of the hydrotalcite-like materials was neutral, and then dried. The carbon dioxide adsorption was measured by a SETLINE thermogravimeter (Setaram).

[0121] The specific test plan is:

[0122] (1) The sample was heated at 400 °C for 3 h in an argon atmosphere at 50 mL / min to activate the layered double hydroxide components and transform them into layered double metal oxides.

[0123] (2) Cooling treatment: when the temperature drops to 200°C, the atmosphere is switched to 50 mL / min carbon dioxide and continued for 2 h. The increased weight of the sample is the chemical adsorption amount of carbon dioxide.

[0124] The statistical unit is based on the weight of the sample after activation per gram. The specific adsorption amount is compared with Figure 4 shown.

[0125] Figure 4 9 bar graphs are shown, representing, from left to right, samples of Comparative Example 1, Comparative Example 2, Example 2, Example 1, Example 4, Example 3, Comparative Example 3, Example 5 and Example 6, respectively.

[0126] From the comparison of Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that after the sample of Example 1 is activated, the adsorption amount of carbon dioxide is 0.25 mmol / g, which is significantly higher than the adsorption amount of carbon dioxide in Comparative Example 1 (0.15 mmol / g) and Comparative Example 2 (0.13 mmol / g), which proves that acid treatment under acidic conditions can improve the conversion rate of layered double metal hydroxides in hydrotalcite-like materials, thereby increasing the unit adsorption amount of carbon dioxide.

[0127] By comparing Example 1 and Comparative Example 3, it can be seen that after the sample of Example 1 is activated, the adsorption amount of carbon dioxide (0.25 mmol / g) is higher than the adsorption amount of carbon dioxide (0.23 mmol / g) of Comparative Example 3, which proves that the acid treatment with a weaker first acid can not only reduce the consumption of sodium hydroxide solution, but also enable the sodium hydroxide solution to be recycled for multiple times, thereby increasing environmental friendliness. Moreover, under the acid treatment conditions of Example 1, the conversion effect of metal elements in blast furnace slag is better, which further improves the conversion rate of the layered double metal hydroxide in the hydrotalcite-like material, thereby further improving the unit adsorption amount of carbon dioxide.

[0128] 3.2.2 Total adsorption of carbon dioxide

[0129] In step (2) of the test of the chemical adsorption of carbon dioxide, the test is performed by first cooling the temperature and then switching the atmosphere. Unlike the test of the chemical adsorption of carbon dioxide, the test of the total adsorption of carbon dioxide is performed by first switching the atmosphere and then cooling the temperature.

[0130] The specific test plan is:

[0131] (1) The sample was heated at 400 °C for 3 h in an argon atmosphere at 50 mL / min to activate the layered double hydroxide components and transform them into layered double metal oxides.

[0132] (2) Switch the atmosphere to 50 mL / min carbon dioxide and cool it down. When the temperature drops to 200°C, continue to introduce 50 mL / min carbon dioxide for 2 h. The increased weight of the sample is the total adsorption of carbon dioxide.

[0133] The statistical unit is based on the weight of the sample after activation per gram. Due to the cooling process from 400℃ to 200℃, a part of the carbon dioxide will be adsorbed in the amorphous layered bimetallic oxide structure to form physical adsorption. The total carbon dioxide adsorption amount minus the previous chemical adsorption amount can be obtained to obtain the physical adsorption amount. Figure 5 shown.

[0134] Figure 5Four bar graphs are shown, representing samples of Comparative Example 1, Example 2, Example 1, and Example 6 from left to right. Figure 5 It can be seen that the advantage of changing the intercalated anion is reflected in the improvement of physical adsorption performance. Therefore, after changing the intercalated anion, the overall adsorption performance of the material is improved.

[0135] The above is a detailed introduction to the preparation method of the hydrotalcite-like material, the hydrotalcite-like material, and the carbon dioxide adsorption material disclosed in the embodiments of the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the preparation method of the hydrotalcite-like material, the hydrotalcite-like material, the carbon dioxide adsorption material and their core ideas of the present invention: At the same time, for those skilled in the art, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A method for preparing a hydrotalcite-like material, characterized in that: The following steps are involved: Acid treatment: mixing and grinding the solid waste material and a first acid having a volume fraction of 20% to 40% in a mass ratio of 1:(0.7 to 5) to obtain a pretreated slurry having a pH of 5 to 7, wherein the solid waste material contains a divalent metal element and a trivalent metal element; Alkali treatment: the pretreated slurry is mixed with a first alkali for reaction, and then subjected to aging treatment to obtain a hydrotalcite-like material.

2. The method for preparing a hydrotalcite-like material according to claim 1, characterized in that: The first acid is a small molecule organic acid, and the small molecule organic acid includes one or more of acetic acid or butyric acid.

3. The method for preparing a hydrotalcite-like material according to claim 1, characterized in that: The first base is an inorganic base containing hydroxide ions, and the inorganic base is one or more of sodium hydroxide or potassium hydroxide.

4. The method for preparing a hydrotalcite-like material according to any one of claims 1 to 3, characterized in that: The concentration of the first alkali is 1-4 mol / L, and the input ratio of the solid waste material to the first alkali is 1 g: (6-60) mL.

5. The method for preparing a hydrotalcite-like material according to claim 4, characterized in that: The solid waste material includes a material containing blast furnace slag; and / or, The mass ratio of the solid waste material to the first acid is 1:(1-1.5); and / or, The concentration of the first base is 1-2 mol / L; and / or, The ratio of the input amount of the solid waste material to the first alkali is 1g: (10-20)mL.

6. The method for preparing a hydrotalcite-like material according to any one of claims 1 to 3, characterized in that: After the aging treatment, the first alkali is recovered, and the recovered first alkali is recycled for use in preparing the hydrotalcite-like material.

7. The method for preparing a hydrotalcite-like material according to any one of claims 1 to 3, characterized in that: In the acid treatment step, the grinding time is 0.5 to 2 hours, and the grinding speed is 300 to 800 rpm; and / or, in the alkali treatment step, the temperature of the mixed reaction of the pretreated slurry and the first alkali is 90°C to 100°C, and the time is 0.5 to 2 hours; and / or, in the alkali treatment step, the aging treatment is room temperature aging for more than 12 hours.

8. The method for preparing a hydrotalcite-like material according to any one of claims 1 to 3, characterized in that: The method for preparing the hydrotalcite-like material further comprises the following steps: After the aging treatment, the intercalation anion treatment is added: The hydrotalcite-like material after the aging treatment is mixed with an organic anion metal salt solution and placed in a protective atmosphere of nitrogen or inert gas, and reacted at 140° C. to 180° C. for 12 to 24 hours to obtain the hydrotalcite-like material with changed intercalated anions.

9. The method for preparing a hydrotalcite-like material according to claim 8, characterized in that: The organic anions in the organic anion metal salt solution are one or more of butyrate ions or acetate ions; and / or, 10 g of the hydrotalcite-like material after the aging treatment is added to every 1 L of the organic anion metal salt solution, and the concentration of the organic anion metal salt solution is 0.1 to 5 mol / L; and / or, after the intercalation anion treatment is changed, the organic anion metal salt solution is recovered, and the recovered organic anion metal salt solution is recycled in the step of changing the intercalation anion treatment.

10. The method for preparing a hydrotalcite-like material according to any one of claims 1 to 3, characterized in that: The average particle size of the solid waste material is 1 to 100 μm.

11. A hydrotalcite-like material, characterized in that: The hydrotalcite-like material is prepared by the method for preparing a hydrotalcite-like material according to any one of claims 1 to 10. The hydrotalcite-like material comprises an alkali silicate and a layered double metal hydroxide, and the layered double metal hydroxide is supported on the surface of the alkali silicate.

12. The hydrotalcite-like material according to claim 11, characterized in that: The layered double metal hydroxide includes divalent metal ions, trivalent metal ions and intercalation anions, the divalent metal ions include one or both of calcium ions and magnesium ions, the trivalent metal ions include aluminum ions, and the intercalation anions include one or more of silicate ions, butyrate ions or acetate ions.

13. A carbon dioxide adsorbent material, characterized in that: The hydrotalcite-like material according to claim 11 or 12 is used to prepare the carbon dioxide adsorption material, wherein the carbon dioxide adsorption material comprises an alkali silicate and a layered bimetallic oxide, wherein the layered bimetallic oxide is loaded on the surface of the alkali silicate, and the layered bimetallic oxide exhibits a nano-petal-like morphology.